Vulnerability of quinoa (Chenopodium quinoa Willd) to environmental stress events in the high Andean regions of Peru - Ccoyllar-Quintanilla, Kevin P. (2021)
Quinoa (Chenopodium quinoa Willd) is an agricultural crop that was domesticated in the Andes of Peru and Bolivia, and that has managed to be produced in any type of soil, characterized by its high amount of nutrients and because it is a species that comes to combat abiotic stresses such as drought, salinity, among others. For example, in the face of drought and high temperatures, this crop becomes very tolerant as it has shown that it uses smaller amounts of water and adapts to fluctuations in the climate during biomass production, which makes it a great alternative for regions, arid and semi-arid. In this sense, the objective of this research article was to determine the vulnerability of the cultivation of quinoa to environmental stress events in the high Andean regions of Peru, through the development and analysis of the current distribution model and its future projections for 2050 and 2070 in scenarios RCP 2.6, RCP 4.5 and RCP 8.5 considering their points of presence and the different bioclimates. Likewise, determine by means of the BAM diagram the optimal zones for its development, considering the abiotic, biotic and accessibility variables. In conclusion, it was obtained that quinoa becomes very tolerant to abiotic stress events such as drought and high temperatures, highlighting as the most optimal areas for its development the departments of Puno, Apurímac, Ayacucho and Cuzco.